2017
DOI: 10.1371/journal.pone.0179424
|View full text |Cite|
|
Sign up to set email alerts
|

Antipsychotic medications and stroke in schizophrenia: A case-crossover study

Abstract: BackgroundThe association between antipsychotic use and the risk of stroke in schizophrenic patients is controversial. We sought to study the association in a nationwide cohort with schizophrenia.MethodsUsing a retrospective cohort of patients with schizophrenia (N = 31,976) derived from the Taiwan National Health Insurance Research Database, 802 new-onset cases of stroke were identified within 10 years of follow-up (from 2000 through 2010). We designed a case-crossover study using 14-day windows to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
0
15
0
4
Order By: Relevance
“…The pharmacokinetic interaction of carbamazepine and first-generation antipsychotics consequently contradicts the synergic effects of these two drugs for the elevated risk of stroke observed in this study. Given that the distinct receptor profiles of antipsychotic medications can contribute to the different level of stroke risk, 13,22 further research with detailed differentiation of prescribed antipsychotic medications is needed to validate our observations.…”
Section: Combination Therapy and The Risk Of Strokementioning
confidence: 84%
See 1 more Smart Citation
“…The pharmacokinetic interaction of carbamazepine and first-generation antipsychotics consequently contradicts the synergic effects of these two drugs for the elevated risk of stroke observed in this study. Given that the distinct receptor profiles of antipsychotic medications can contribute to the different level of stroke risk, 13,22 further research with detailed differentiation of prescribed antipsychotic medications is needed to validate our observations.…”
Section: Combination Therapy and The Risk Of Strokementioning
confidence: 84%
“…Concomitant drugs included cardiovascular drugs, drugs used in diabetes, antithrombotic agents, respiratory drugs, corticosteroids, antipsychotics, antidepressants and benzodiazepines. These factors were selected because of their potential association with the risk of stroke 13 …”
Section: Methodsmentioning
confidence: 99%
“…Poorer secondary prevention has been shown previously in ischemic heart disease (16), and a study from the US reported that the Framingham 10-year risk of coronary heart disease was increased by 79% in patients with schizophrenia (9). One potential driver of poorer cardiovascular health in these patients could be the cardiovascular side effects of antipsychotic drugs (13, 22).…”
Section: Discussionmentioning
confidence: 99%
“…Use of antidiabetic drugs, antihypertensives, lipid lowering agents, antiplatelets, oral anticoagulants, non-steroidal anti-inflammatory drugs, and antipsychotics were grouped according to the anatomical therapeutic chemical classification system ( S3 Table ). Non-steroidal anti-inflammatory drugs and antipsychotics were evaluated because they have been found to increase the risk of ischemic stroke [ 15 18 ].…”
Section: Methodsmentioning
confidence: 99%